Reflections on the journey: six short stories - Haynie, Sharon L (BioMed Central, 2011)
One of the goals of the 2011 International Year of Chemistry is to celebrate the contributions of women to science. A question that has been frequently asked in this regard is... Why is it necessary to highlight women in the "age of equality"? The reasons are varied but the facts are that many women scientists worked in obscurity throughout the 19(th )and even well into the 20(th )century, sometimes publishing anonymously to be heard. This celebration of Women in Science is one way to recognize both the resiliency and passion of these women. As part of this celebration, Chemistry Central Journal's Thematic Series of "Women in Chemistry" includes this article describing the path several women took as they pursued chemistry careers spanning the latter part of the 20(th )century and into the early 21(st )century. Sharon Haynie, Nancy Jones, Cheryl Martin, Paula Olsiewski, Mary Roberts and Amber Hinkle each have unique story of their personal journey from childhood to adulthood. As you read these stories, listen generously, and feel free to share your own stories, comments and thoughts.